How do you differentiate cos^2(x^3)cos2(x3)?

1 Answer
Nov 2, 2016

(cos^2(x^3))'=-3x^2sin(2x^3)

Explanation:

The differentiation of the given function is determined by applying chain rule

Let u(x)=cos^2x and v(x)=x^3
Then the given function is a composite of u(x) and v(x)

color(blue)(u@v(x)=u(v(x))=cos^2(x^3))

color(red)((u@v(x))'=u'(v(x))=xxv'(x))

(cos^2(x^3))'=(cos^2)'(v(x))xx(x^3)'

(cos^2(x^3))'=(2(-sin(v(x)))cos(v(x))xx(3x^2)

(cos^2(x^3))'=-2sin(x^3)cos(x^3)xx(3x^2)

(cos^2(x^3))'=-color(brown)(sin(2x^3))xx(3x^2)

(cos^2(x^3))'=-3x^2sin(2x^3)